A structural equation modeling of customer attitudes towards residential solar initiatives in Jordan - Haneen Abuzaid; Lama AbuMoeilak; Ayman Alzaatreh (Social Sciences and Humanities Open)
Photovoltaic (PV) systems have gained global significance as a sustainable and renewable energy resource, playing a pivotal role in mitigating climate change and meeting growing energy demands. Like many other nations, Jordan recognizes the potential of PV systems and has been actively pursuing their adoption across various sectors, particularly in the residential sector. This paper aims to investigate the factors influencing residential customers' perceptions of PV systems and their intentions to adopt these systems in Jordan by identifying key determinants of perception and adoption and developing a comprehensive Structural Equation Model (SEM) to quantify the relationships between identified factors and their effect on the intention to adopt residential PV systems. A theoretical model was developed to achieve the study's objectives, employing confirmatory factor analysis and structural equation modeling. Data for this study was collected through a comprehensive survey targeting the residential segment. The findings indicate that social, technological, governmental, and financial factors positively and statistically significantly impact residential customers' perceptions of PV systems, fostering their intention to embrace this technology. Surprisingly, the environmental factor was deemed insignificant in influencing residential customers' decision-making processes. This research offers valuable insights to various stakeholders, including PV contractors, consultants, governmental entities, policy, and decision-makers. By understanding the key drivers and barriers shaping residential PV adoption, stakeholders can devise more effective strategies to promote sustainable energy practices, foster economic growth, and contribute to the global transition towards cleaner energy sources.